The role of NF-kB in the mechanisms of inflammation of the stomach's mucosa in children - V.І. Bobrova (Group of Companies Med Expert, LLC, 2023)
Introduction. One of the important and unresolved issues of pediatric gastroenterology remains study of inflammation mechanisms of the stomach's mucosa, as well as factors that regulate inflammatory reactions. Nowadays, there are many studies devoted to the research of the nuclear role of factor kappa B (NF-kB) in the regulation of the level of gene expression that control proliferation, cell apoptosis, angiogenesis, and determine the nature and expressiveness of the inflammatory process in adults. However, there are no conclusion regardless the role of NF-kB in the regulation of the mechanisms of inflammation development in the stomach's mucosa of chronic gastritis (CG) in children. Purpose - to study the level of NF-κB activity depending on the degree of gastric mucosa inflammation of chronic gastritis in children. Materials and methods. We observed 76 children aged 8-16 years with verified chronic gastritis. To verify the diagnosis, all children underwent a morphological examination of the stomach's mucosa in the fundal and antral departments of the stomach. An indirect streptavidin-peroxidase method of protection using polyclonal antibodies to NF-kB was used for immunohistochemical research. Results. On the basis of the morphological study of gastric biopsies, we discovered inflammatory changes based of lymphocytic infiltration, microcirculatory disorders of the stomach's mucosa with the subsequent development of stroma lamina propria fibrosis. During the immunohistochemical study of gastric biopsies, a high level of NF-kB expression was noted in the cytoplasm with a pronounced degree of inflammation, atrophy, and lymphocytic infiltration of the stomach's mucosa. Conclusions. The results of the study indicate the morphological signs of the formation of an early chronic inflammatory process in gastritis in children. The transcription factor NF-kB determines the level of inflammatory activity and plays a leading role in the mechanism of development of chronic gastritis in children. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the author.